2005
DOI: 10.1111/j.1532-5415.2005.53169.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Subjective Social Status and Measures of Health in Older Taiwanese Persons

Abstract: A simple subjective assessment of one's ranking on the social hierarchy was associated with self-rated health and physical functional status in an older ethnic Chinese population. The associations were independent of the effects of traditional objective measures of SES, such as education, income, and occupation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
146
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 32 publications
14
146
2
5
Order By: Relevance
“…This evidence suggests that SSS and wealth, regardless of their overlap, were important correlates of older people's health independent of one another. This conclusion coincides with recent suggestions that objective and subjective measures of SES are related but not interchangeable (Hu et al, 2005) and indicates that SSS and wealth reflect cumulative SES but probably different dimensions of it.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This evidence suggests that SSS and wealth, regardless of their overlap, were important correlates of older people's health independent of one another. This conclusion coincides with recent suggestions that objective and subjective measures of SES are related but not interchangeable (Hu et al, 2005) and indicates that SSS and wealth reflect cumulative SES but probably different dimensions of it.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we found that the associations of SSS with waist circumference and CRP in women and with fibrinogen in men became non-significant only in models that adjusted for all objective SES measures. These findings accord with the existing literature suggesting that SSS is related to self-rated health (Franzini & Fernandez-Esquer, 2006;Hu et al, 2005;Operario et al, 2004;Ostrove et al, 2000;Singh-Manoux et al, 2005) and mental health (Franzini & FernandezEsquer, 2006;Singh-Manoux et al, 2005). However, they are not consistent with evidence suggesting that SSS is not related to diabetes in women over and above education (SinghManoux et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations